Engineering Yarrowia lipolytica as a Chassis for De Novo Synthesis of Five Aromatic-Derived Natural Products and Chemicals - Gu, Yang; Ma, Jingbo; Zhu, Yonglian; Ding, Xinyu; Xu, Peng (ACS synthetic biology, 2020)
Yarrowia lipolytica is a novel microbial chassis to upgrade renewable low-cost carbon feedstocks to high-value commodity chemicals and natural products. In this work, we systematically characterized and removed the rate-limiting steps of the shikimate pathway and achieved de novo synthesis of five aromatic chemicals in Y. lipolytica. We determined that eliminating amino acids formation and engineering feedback-insensitive DAHP synthases are critical steps to mitigate precursor competition and relieve the feedback regulation of the shikimate pathway. Further overexpression of heterologous phosphoketolase and deletion of pyruvate kinase provided a sustained metabolic driving force that channels E4P (erythrose 4-phosphate) and PEP (phosphoenolpyruvate) precursors through the shikimate pathway. Precursor competing pathways and byproduct formation pathways were also blocked by inactivating chromosomal genes. To demonstrate the utility of our engineered chassis strain, three natural products, 2-phenylethanol (2-PE), p-coumaric acid, and violacein, which were derived from phenylalanine, tyrosine, and tryptophan, respectively, were chosen to test the chassis performance. We obtained 2426.22 ± 48.33 mg/L of 2-PE, 593.53 ± 28.75 mg/L of p-coumaric acid, 12.67 ± 2.23 mg/L of resveratrol, 366.30 ± 28.99 mg/L of violacein, and 55.12 ± 2.81 mg/L of deoxyviolacein from glucose in a shake flask. The 2-PE production represents a 286-fold increase over the initial strain (8.48 ± 0.50 mg/L). Specifically, we obtained the highest 2-PE, violacein, and deoxyviolacein titer ever reported from the de novo shikimate pathway in yeast. These results set up a new stage of engineering Y. lipolytica as a sustainable biorefinery chassis strain for de novo synthesis of aromatic compounds with economic values.Yarrowia lipolytica is a novel microbial chassis to upgrade renewable low-cost carbon feedstocks to high-value commodity chemicals and natural products. In this work, we systematically characterized and removed the rate-limiting steps of the shikimate pathway and achieved de novo synthesis of five aromatic chemicals in Y. lipolytica. We determined that eliminating amino acids formation and engineering feedback-insensitive DAHP synthases are critical steps to mitigate precursor competition and relieve the feedback regulation of the shikimate pathway. Further overexpression of heterologous phosphoketolase and deletion of pyruvate kinase provided a sustained metabolic driving force that channels E4P (erythrose 4-phosphate) and PEP (phosphoenolpyruvate) precursors through the shikimate pathway. Precursor competing pathways and byproduct formation pathways were also blocked by inactivating chromosomal genes. To demonstrate the utility of our engineered chassis strain, three natural products, 2-phenylethanol (2-PE), p-coumaric acid, and violacein, which were derived from phenylalanine, tyrosine, and tryptophan, respectively, were chosen to test the chassis performance. We obtained 2426.22 ± 48.33 mg/L of 2-PE, 593.53 ± 28.75 mg/L of p-coumaric acid, 12.67 ± 2.23 mg/L of resveratrol, 366.30 ± 28.99 mg/L of violacein, and 55.12 ± 2.81 mg/L of deoxyviolacein from glucose in a shake flask. The 2-PE production represents a 286-fold increase over the initial strain (8.48 ± 0.50 mg/L). Specifically, we obtained the highest 2-PE, violacein, and deoxyviolacein titer ever reported from the de novo shikimate pathway in yeast. These results set up a new stage of engineering Y. lipolytica as a sustainable biorefinery chassis strain for de novo synthesis of aromatic compounds with economic values.